Pluralisme Hukum di Yaman: Pergulatan Antara Syariah Islam dan Hukum Positif di Tengah Krisis Politik dan Kemanusiaan - Nurhidayah Nurhidayah; Asasriwarni Asasriwarni; Zulfan Zulfan (STIS Ummul Ayman, Pidie Jaya, Aceh, Indonesia, 2026)
This study examines the legal pluralism in Yemen, which develops through a complex interaction between Islamic law (sharia), state law (qanun), and tribal customary law (‘urf) amidst a prolonged political and humanitarian crisis. These three legal systems operate not only in parallel but also in competition to establish authority, legitimacy, and mechanisms for dispute resolution. The purpose of this research is to analyze the structure, dynamics, and dialectics of these legal systems as well as their impacts on society, particularly vulnerable groups such as women and children. This study employs a qualitative descriptive method based on library research using primary sources including Yemeni legal documents, international reports, and recent academic studies. The findings reveal that sharia remains dominant in family law, state law governs civil and economic sectors, and customary law plays a significant role in local dispute settlement during the weakening of state institutions. Armed conflict intensifies legal fragmentation, creating severe uncertainty in access to justice while enabling militias to politicize legal institutions. The study concludes that Yemen’s legal pluralism is hybrid, dynamic, yet fragile, as it is not supported by a stable state structure. Therefore, reconstructing Yemen’s legal framework requires harmonizing sharia, state law, and customary law through institutional reform, strengthening the rule of law, and ensuring protection for vulnerable groups. This study also recommends a reconstructive approach that incorporates local values and modern legal standards to build a more inclusive, adaptive, and resilient legal system for Yemen.